ANALYSIS OF PERSON'S PROBLEM-SOLVING SKILLS - Munali, Munali; Liberna, Hawa; Mutakin, Tatan Zenal (Prima: Jurnal Pendidikan Matematika, 2024)
This research is part of the development of an essay item instrument for problem-solving skills in the Basic Mathematics Course. Measuring the ability of Mathematics problem-solving skills was carried out on 298 students of the Information Systems Study Program at Indraprastha University PGRI Jakarta, Odd Semester, Academic Year 2023-2024. This research aims to analyze the person's ability to solve problems in the Basic Mathematics Subject with 15 questions. The dimensions of problem-solving skills include two dimensions, namely: 1) observation skills and 2) critical thinking skills. This research uses a quantitative research methodology with an analysis of a person's abilities using the Rasch Model. The results of the research are: 1) there are 271 valid people out of 298 people, 2) person number 109 is the person with the highest ability, namely 0.23 logit, and person number 14 is the person with the lowest ability, namely -4.21 logit, 3) Cronbach's Alpha (KR-20) person reliability score is 0.77, meaning that the person reliability coefficient score can holistically be categorized as good and acceptable, 3) person reliability score is 0.85, meaning that person reliability can be categorized as good and acceptable. , 4) the mean person measure score is -1.16 logit < 0.00 logit indicating the student's ability is less than the level of difficulty of the item, and 5) the accuracy of the person's ability to respond to problem-solving skills is 22% in the low category. Based on the results of this research, it can be concluded that: students' problem-solving skills are in the low category. To improve people's abilities by getting students used to solving mathematical problems related to everyday life.Keywords:21st Century Learning, Problem Solving Skills, Rasch Model